Arabinogalactan protein 31 (AGP31), a putative network-forming protein in Arabidopsis thaliana cell walls? - Hijazi, May; Roujol, David; Nguyen-Kim, Huan; Cisneros Castillo, Liliana del Rocío; Saland, Estelle; Jamet, Elisabeth; Albenne, Cécile (Annals of botany, 2014)
Arabinogalactan protein 31 (AGP31) is a remarkable plant cell-wall protein displaying a multi-domain organization unique in Arabidopsis thaliana: it comprises a predicted signal peptide (SP), a short AGP domain of seven amino acids, a His-stretch, a Pro-rich domain and a PAC (PRP-AGP containing Cys) domain. AGP31 displays different O-glycosylation patterns with arabinogalactans on the AGP domain and Hyp-O-Gal/Ara-rich motifs on the Pro-rich domain. AGP31 has been identified as an abundant protein in cell walls of etiolated hypocotyls, but its function has not been investigated thus far. Literature data suggest that AGP31 may interact with cell-wall components. The purpose of the present study was to identify AGP31 partners to gain new insight into its function in cell walls.Nitrocellulose membranes were prepared by spotting different polysaccharides, which were either obtained commercially or extracted from cell walls of Arabidopsis thaliana and Brachypodium distachyon. After validation of the arrays, in vitro interaction assays were carried out by probing the membranes with purified native AGP31 or recombinant PAC-V5-6xHis. In addition, dynamic light scattering (DLS) analyses were carried out on an AGP31 purified fraction.It was demonstrated that AGP31 interacts through its PAC domain with galactans that are branches of rhamnogalacturonan I. This is the first experimental evidence that a PAC domain, also found as an entire protein or a domain of AGP31 homologues, can bind carbohydrates. AGP31 was also found to bind methylesterified polygalacturonic acid, possibly through its His-stretch. Finally, AGP31 was able to interact with itself in vitro through its PAC domain. DLS data showed that AGP31 forms aggregates in solution, corroborating the hypothesis of an auto-assembly.These results allow the proposal of a model of interactions of AGP31 with different cell-wall components, in which AGP31 participates in complex supra-molecular scaffolds. Such scaffolds could contribute to the strengthening of cell walls of quickly growing organs such as etiolated hypocotyls.
Gesehen am 19.01.2021